(untitled) (Journal of Applied Botany and Food Quality, 2016)
The non-protein amino acid beta-aminobutyric acid (BABA) enhances squash resistance to microbial pathogens through potentiation of the squash defense responses. In the present study, we investigated the effects of BABA pretreatment on cucurbit powdery mildew disease. Three concentrations of BABA (0.5, 2 and 4mM) as priming media and distilled water as control plants were used. The results showed that the 4mM BABA was the most effective concentration to control the disease symptom. The expression of PR-1 genes in relation with this pathogen was investigated and confirmed. The Guaiacol peroxidase and Phenylalanine amonia-lyase enzyme activities increased in pretreated-inoculated squash plants. Bases on our results and regarding the adverse effects of fungicide on environment, use of BABA as environmentally safe agent a valuable contribution to disease management is recommended.